2008
DOI: 10.1093/nar/gkn380
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecularly folded G-quadruplex and i-motif structures in the proximal promoter of the vascular endothelial growth factor gene

Abstract: A polyguanine/polycytosine (polyG/polyC) tract in the proximal promoter of the vascular endothelial growth factor (VEGF) gene is essential for transcriptional activation. The guanine-rich (G-rich) and cytosine-rich (C-rich) strands on this tract are shown to form specific secondary structures, characterized as G-quadruplexes and i-motifs, respectively. Mutational analysis of the G-rich strand combined with dimethyl sulfate (DMS) footprinting, a polymerase stop assay, and circular dichroism (CD) spectroscopy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
162
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 49 publications
7
162
1
1
Order By: Relevance
“…2C, Top, red arrowhead). Previous studies showed that such hypercleavages could occur at the Gs in the terminal G-quartet of a G-quadruplex, and the reason for that was not clear (22). Addition of GMP to the DNA did not alter the cleavage (blue vs. green peak).…”
Section: Resultsmentioning
confidence: 85%
“…2C, Top, red arrowhead). Previous studies showed that such hypercleavages could occur at the Gs in the terminal G-quartet of a G-quadruplex, and the reason for that was not clear (22). Addition of GMP to the DNA did not alter the cleavage (blue vs. green peak).…”
Section: Resultsmentioning
confidence: 85%
“…It is evident that the spectra exhibited significant changes concomitant with pH change from 7.5 to 4.5. The CD spectra showed a large increase in ellipticity with a positive band near 288 nm and a negative peak at 262 nm at pH 4.5 and 5.5, which are the hallmark characteristics of i-motif structure (91)(92)(93). At pH 7.5, the positive maxima shifted to 278-280 nm with a drastic decrease in molar ellipticity, consistent with an unordered random-coiled structure.…”
Section: Resultsmentioning
confidence: 87%
“…Besides these above-mentioned i-Motifs, there are other promoter iMotifs that have been under study, like vascular endothelial growth factor promoter region can form an i-Motif in vitro at acidic pH [14].…”
Section: Editorialmentioning
confidence: 99%